Agricultural Production with Uncertain Water Supply - John K. Dagsvik; Astrid L. Mathiassen (Statistics Norway, Research Department, 2004)
The purpose of this paper is to develop a framework for analysis of multioutput agricultural production when the supply of water is uncertain. Specifically, we assume that the farmer operates as if the decision process takes place in two stages. In stage one the farmer decides how much land to allocate to each crop. However, in this stage he is uncertain about the supply of water during the growth period before harvest. In the second stage when the uncertainty is revealed he adjusts the quantities of (ex-post) input factors (given the allocation in the first stage). The production technology is assumed to be of the Leontief type. We also extend the model to the case with several seasons where one crop is cultivated throughout all season while the remaining crops are seasonal-specific. The empirical model is extended to allow for a particular version of bounded rationality in which the farmer is allowed to make optimization error. This implies that the estimation procedure is considerably simplified.
Keywords: D21; N50; 330; Multioutput agricultural production; Uncertain water supply; Land constraints; Continuous random utility model; Leontief technology.